Sixteen-Pixel NbN Nanowire Single Photon Detector Coupled With 300-μm Fiber - Qi Chen; Biao Zhang; Labao Zhang; Rui Ge; Ruiying Xu; Yang Wu; Xuecou Tu; Xiaoqing Jia; Danfeng Pan; Lin Kang; Jian Chen; Peiheng Wu (IEEE Photonics Journal)
Niobium nitride (NbN) nanowires have a high repetition rate and efficiency, making them ideal for superconducting nanowire single photon detectors (SNSPDs). However, it is difficult to fabricate NbN arrays over large areas, which is critical for various applications. This paper describes a 4 × 4 NbN SNSPD array (16 pixels) and optical coupling with a 300-μm-diameter multimode fiber using beam compression technology. This is the first NbN SNSPD coupled with such large-diameter fibers. The designed pixels are positioned as closely as possible (pixel filling factor about 98.5%), almost without dead area between them. This results in a system efficiency of 46% and a quantum efficiency of 94.5% for photons (λ = 1064 nm) coupled from multimode fibers. An intrinsic time resolution of less than 69 ps can be obtained. The proposed high-performance single photon detector is suitable for satellite laser ranging. Furthermore, the proposed system is feasible for large SNSPD arrays with NbN, paving the way for the development of efficient photon cameras with NbN nanowires.